Immediate Postoperative Treatment of Keloids with Intraoperative Radiation Therapy Technology: A Pilot Study. Issue 9 (September 2021) - Tresoldi, Marco Mario; Ivaldi, Giovanni Battista; Porcu, Patrizia; Randisi, Fabio; Cartocci, Andrea; Malovini, Alberto; Faga, Angela; Nicoletti, Giovanni
Abstract : Background: The combination of surgery and postoperative radiotherapy allows for the most effective results with keloids. In this trial, surgery and intraoperative radiation therapy (IORT) technology were used—the hypothesis being that the earlier the application of postoperative radiotherapy, the better the wound healing evolution. Methods: The study included 16 patients with 21 keloids. The keloids were radically excised and repaired with direct suture or local skin flaps. Collimated electron radiotherapy was applied within 45 minutes of surgery. The outcomes were assessed according to the modified Patient and Observer Scar Assessment Scale; the modified Vancouver Scar Scale; and the modified Common Terminology Criteria for Adverse Events v. 4.0 for skin and subcutaneous tissue disorders. Results: Recurrences were observed in one out of 16 patients, and in two out of 21 keloids (9.5%). The modified Patient and Observer Scar Assessment Scale demonstrated a statistically significant improvement in pain, itching, color, stiffness, thickness, and irregularity after the treatment. The modified Patient and Observer Scar Assessment Scale displayed a statistically significant improvement in the scar vascularity, pigmentation, thickness, and pliability after the treatment. The modified Vancouver Scar Scale demonstrated a statistically significant improvement in 90.48% of the scars after the treatment. The modified Common Terminology Criteria for Adverse Events v. 4.0 for skin and subcutaneous tissue disorders demonstrated an improvement in erythema multiforme and skin pain across the whole sample, with a temporary hyperpigmentation in 19% of the scars after the treatment. Conclusion: The combination of surgery and collimated electron radiotherapy with IORT technology demonstrated favorable results in 90.5% of the cases.